Outcomes of snuffbox arteriovenous fistula as a first-line approach to dialysis access in patients with end-stage kidney disease - Mohamed H. Khalaf (22225009) (2025)
Objective The persistent shortage of organs for kidney transplantation necessitates long-term renal replacement therapies like hemodialysis. Arteriovenous fistula (AVF) creation is a well-established method for vascular access to be used for hemodialysis, with the wrist radiocephalic AVF being common. Although the anatomical snuffbox radiocephalic AVF is less frequently used, it remains a potential site for AVF creation. The objective of this study was to evaluate our long-term outcomes of using the snuffbox AVF as a first-line approach for vascular access in patients with end-stage kidney disease. Methods This retrospective single-center study included all patients undergoing primary snuffbox AVF creation at our institution from November 2005 to December 2022. Preoperative ultrasound assessed vessel suitability for the procedure. Procedures were performed under local anesthesia with procedural sedation, involving dissection of the radial artery and cephalic vein within the anatomical snuffbox, and side-to-side anastomosis. Post-procedure, patients were followed for fistula patency. Data collected included demographics, baseline laboratory values, comorbidities, previous vascular access, and anticoagulant use. Primary patency and primary assisted patency was analyzed. Results Snuffbox AVF procedures were performed on 258 patients (77.9% male; median age, 53 years). Primary patency rates were 94% at 1 month, 87% at 6 months, and 79% at 1 year. 6.6% of patients required endovascular intervention, and 18.6% underwent kidney transplantation. No deaths were related to fistula creation. Conclusions Snuffbox AVFs are a safe and viable alternative to wrist AVF in suitable candidates, demonstrating comparable rates of complications and patency. Snuffbox AVFs can help patients maintain long-term vascular access for dialysis and while awaiting transplant. Other Information Published in: Journal of Vascular Surgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jvs.2025.09.040